2019
DOI: 10.1111/bioe.12549
|View full text |Cite
|
Sign up to set email alerts
|

The role of data custodians in establishing and maintaining social licence for health research

Abstract: In this article we explore the role of data custodians in establishing and maintaining social licence for the use of personal information in health research. Personal information from population‐level data collections can be used to make significant contributions to health and medical research, but this use is dependent on community acceptance or a social licence. We conducted semi‐structured interviews with data custodians across Australia to better understand data custodians’ views on their roles and respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In response to high profile public controversies around data use (and misuse), recent years have brought calls to establish a SL for data practices (e.g. Allen et al, 2019, Carter et al, 2015Lawler et al, 2018;Leonard, 2018). For example, the New Zealand Government established the Data Futures Partnership to develop guidelines that public and private organisations can use to develop a SL for data use (Data Futures Partnership, 2017).…”
Section: A Social Licence For Data Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to high profile public controversies around data use (and misuse), recent years have brought calls to establish a SL for data practices (e.g. Allen et al, 2019, Carter et al, 2015Lawler et al, 2018;Leonard, 2018). For example, the New Zealand Government established the Data Futures Partnership to develop guidelines that public and private organisations can use to develop a SL for data use (Data Futures Partnership, 2017).…”
Section: A Social Licence For Data Practicesmentioning
confidence: 99%
“…A recent international consensus statement set out the importance of public engagement to establishing a SL for data-intensive health research (Aitken et al, 2019); recent research into public attitudes towards research uses of health data have been framed in terms of understanding the conditions needed to ensure a SL for secondary uses of data (e.g. Paprica et al, 2019) and Allen et al (2019) have discussed the role of data custodians in establishing and maintaining a SL for the use of personal information in health research.…”
Section: A Social Licence For Data Practicesmentioning
confidence: 99%
“…If RECs/IRBs decline to grant a waiver of consent, researchers must abandon the research or re-consent all patients and participants whose tissue or data is included in the dataset. Previous research has shown RECs feel a heavy burden of responsibility to protect patients' and publics' interests when patient consent is not sought [15,16].…”
Section: Plos Onementioning
confidence: 99%
“…The concept of a social licence refers to a privilege to operate, implicitly granted by society to an organisation or profession, often in the absence of explicit consent. 6 It refers to a practice that broader publics are willing to accept as morally and socially permissible. Identifying the boundaries of the social licence is di cult; and this is often most evident when activities overstep this boundary and there is a subsequent public backlash.…”
Section: And the China Precisionmentioning
confidence: 99%